Ground Water Quality Analysis and Mapping Using ArcGIS: A Case Study Near Mandur Dumping Site, Bangalore - George, Geena; N. V., Shobha (AMC Indian Journal of Civil Engineering, 2021)
Ground water is very much needed and greatest in amount among all the natural resources for maintaining ecological balance and there is chance of it getting polluted directly or indirectly due to anthropogenic activities. Due to the waste set down at the landfill, ground water contamination can emerge on the porous ground surface and the associated aquifer unreliable for domestic water supply and other uses from the percolation of leachate. In the current study, investigation is conducted on the quality of ground water due to Mandur waste dumping yard (latitude 77°43’E longitude 13°45’N) in Bangalore East, District, Karnataka, India is considered. Water quality parameters such as pH, acidity, alkalinity, dissolved oxygen, chlorides, and hardness were considered for the study. The water samples were collected from bore-wells in and around the dumping site with a radius of 3 km with dumping yard as the centre point. The parameters analyzed were compared with Bureau of Indian Standards and WHO standards to understand the suitability for drinking purpose. ArcGIS is considered an effective tool for mapping of ground water quality and evaluates groundwater vulnerability to pollution. After the water analysis, results obtained are shown in the maps using ArcGIS, which gives a good judgement of present water quality of the current study area. The IDW maps showing the spatial distribution of the above mentioned physical-chemical parameters were done using ArcGIS, which were helpful to the people in identifying the zones of drinking water quality.